ANALYSIS OF CROSS-BORDER PROJECTS BETWEEN FRANCE AND SPAIN 2007-2013 - STAKEHOLDERS AND TERRITORIAL IMPACT - Jaume FELIU; Matteo BERZI; Joan VICENTE; Mita CASTAÑER; Rafel LLUSSÀ (European Journal of Geography)
The overall aim of this research is to study the dynamics of economic and territorial development in the cross-border spaces along the border between France and Spain. In particular, it analyses the characteristics of INTERREG IV-A cross-border cooperation projects in the period 2007-2013. It explores these as an example of the dynamics produced between stakeholders and development projects on both sides of the border. To this effect, a database system was set up in order to transfer all the information on the projects and then to extract concise quantitative and cartographic information, using the possibilities offered by geographic analysis systems.